Integrated coconut farming system for stable income - Maheswarappa, H P; Subramanian, P; Chowdappa, P (Indian Horticulture, 2018)
Coconut gardens offer excellent opportunities to exploit the interspace potential  for maximizing return per unit area. Coconut-based cropping/farming systems   involving cultivation of compatible crops in interspaces of coconut and   integration with other enterprises like dairying offer considerable scope for   increasing production and productivity per unit area, time and inputs by more   efficient utilization of resources like sunlight, soil, water and labour. In humid   tropics, higher efficiency of utilization of the basic resources of crop production,   land, solar radiation and water can be achieved by adopting intensive cropping   systems. Cropping/farming system aims at crop diversification and intensive   cropping in the interspace available in coconut to increase the per palm   productivity as well as productivity of unit holding in a system approach wherein   the available farm resources like soil and water/rainfall resource, farm labour,   agricultural inputs (seeds, fertilizers, agro-chemicals) etc. are utilized to produce   both nuts, food and non-food agricultural products from the farm, in a business   or profitable way. Under such a cropping/farming system, all the management   practices and component production systems should be able to maintain high   productivity, profitability and sustainability of existing coconut palms to maximize   economic yield of the farm. Sustainability is the main objective of farming   system, where production process is optimized through efficient utilization of   the inputs in safeguarding the environment.